2019
DOI: 10.1155/2019/8715718
|View full text |Cite
|
Sign up to set email alerts
|

Mini-Extruder for 3D Magnetoactive Polymer Printing

Abstract: This work describes the development of a new miniature extruder, essential to cavity-free 3D printing of silicone-based smart materials. This makes the 3D printing of magnetoactive and electroactive polymer soft robotic components and devices directly from CAD data possible. The special feature of such an extruder is that it is designed for use with addition-crosslinking RTV-2 silicones, including solid particulate additives. The extruder merges the respective components automatically during extrusion which ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Likewise, a composite filament of Fe 3 O 4 nanoparticles and PLA was produced via melt compounding [ 260 ]. The processing factors such as melting, mixing, homogenization, granulation of compounds, and viscosity for extrusion play a vital role to produce composite filaments and there are a number of other different studies where the influence and optimization of these parameters are well reported, see Dohmen et al [ 261 ], and others [ 262 , 263 , 264 ]. After the extrusion, cross-sectional morphology must be studied to investigate the homogeneity of the filler-matrix system.…”
Section: Towards Magneto-active 4d Printingmentioning
confidence: 99%
“…Likewise, a composite filament of Fe 3 O 4 nanoparticles and PLA was produced via melt compounding [ 260 ]. The processing factors such as melting, mixing, homogenization, granulation of compounds, and viscosity for extrusion play a vital role to produce composite filaments and there are a number of other different studies where the influence and optimization of these parameters are well reported, see Dohmen et al [ 261 ], and others [ 262 , 263 , 264 ]. After the extrusion, cross-sectional morphology must be studied to investigate the homogeneity of the filler-matrix system.…”
Section: Towards Magneto-active 4d Printingmentioning
confidence: 99%
“…Using X-ray micro-tomography, at least one research group has been able to acquire information concerning structure formation in order to quantify particle dimensions, concentration, and structural changes at a particle scale [28,31,32,42]. With the help of 3D printers, new structured and wellorganized MREs are producible [11,14,43,44]. Simulation has assisted greatly in the computation of particle movement as well as magnetostrictive effects, thus helping to complete the overall understanding of MRE deformation mechanisms [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…This interesting research scenario actively promotes the production, optimization and application of innovative materials with tailored or improved functionalities [4]. Those materials include hydrogels, covalent adaptive network materials [5], photomechanical materials [6], shape-memory alloys, electroactive and magnetoactive materials [7], self-cleaning and self-healing materials, among others [1].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly interesting are magnetoactive smart materials [7,8]. Magnetoactive materials have been used for more than two thousand years (202 BC-220 AD), initially for magnetic compasses [9] and nowadays as essential components for motors, generators and electronic devices [10].…”
Section: Introductionmentioning
confidence: 99%